2006
DOI: 10.2527/2006.842433x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplements that contain increasing amounts of metabolizable protein with or without Ca-propionate salt on postpartum interval and nutrient partitioning in young beef cows1

Abstract: Cattle grazing winter range forages exhibit interannual variation in response to supplementation. This variation may be mediated by circulating concentrations and subsequent metabolism of glucose, which are influenced by forage quality and availability. A study conducted at the Corona Range and Livestock Research Center during 2 dry years evaluated responses of young postpartum beef cows (n = 51, initial BW = 408 +/- 3 kg, and BCS = 5.1 +/- 0.04 in year 1; n = 36, initial BW = 393 +/- 4 kg, and BCS = 4.5 +/- 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 35 publications
5
32
3
Order By: Relevance
“…Due to a concurrent drought at time this study was conducted cows and calves were sold after samples were collected and no reproductive assessments were conducted. Cows were individually milked with a portable milking machine at approximately d 90 postpartum following daily feeding of hay on a day after protein supplementation using a modified weigh-suckle-weigh technique [5]. Cows were injected with 1 mL of oxytocin (20 IU; Vedo, Inc., St. Joseph, MO) i.m.…”
Section: Methodsmentioning
confidence: 99%
“…Due to a concurrent drought at time this study was conducted cows and calves were sold after samples were collected and no reproductive assessments were conducted. Cows were individually milked with a portable milking machine at approximately d 90 postpartum following daily feeding of hay on a day after protein supplementation using a modified weigh-suckle-weigh technique [5]. Cows were injected with 1 mL of oxytocin (20 IU; Vedo, Inc., St. Joseph, MO) i.m.…”
Section: Methodsmentioning
confidence: 99%
“…Similar responses to DIP and MP were observed, as previously discussed, when MOEF was adjusted. In ad- dition, we evaluated results from Waterman et al (2006) for young lactating cows in a southwestern production system and observed poor agreement with actual vs. predicted 1996 Beef NRC ADG. The Beef NRC predicted the young lactating cows would lose 1.26 kg/d, whereas cows actually only lost 0.7 kg/d.…”
Section: Current Beef Nrc Predictions and The Existing Datamentioning
confidence: 99%
“…Both primary sources of dietary protein contribute to the MP supply delivered to the host animal, as will be discussed in subsequent paragraphs. Nutrient partitioning can be influenced by the type of protein supplied (Hunter and Magner, 1988;Miner and Petersen, 1989;Miner et al, 1990), the use of rumen-protected AA (Richardson and Hatfield, 1978;Waterman et al, 2007bWaterman et al, , 2012, or a supplement that supplies specific nutrients that target both an energy and protein deficiency in the host animal (Waterman et al, 2006;Mulliniks et al, 2011Mulliniks et al, , 2013.…”
Section: Need For Accurate Prediction Modelsmentioning
confidence: 99%
“…Milk collection began~27 days (earliest date to acquire selection criteria previously mentioned) after parturition (average 16 April each year) and continued at 14-day intervals for 112 days using a technique previously described (Waterman et al, 2006). In brief, on the day of each milking, cows were gathered from pasture, calves were removed and cows were administered an i.m.…”
Section: Measurementsmentioning
confidence: 99%
“…Weight of milk from the second milking was recorded, and an aliquot (20 ml) was retained for analysis of milk protein, lactose, fat, solids non-fat and milk urea N by Rocky Mountain DHIA (Logan, UT, USA). Daily milk yield was estimated from the 4 h milk production yield (kg/day) and composition (g/day) was calculated by multiplying Waterman, Geary, Petersen and MacNeil constituent concentration by daily milk production (Appeddu et al, 1997;Waterman et al, 2006).…”
Section: Measurementsmentioning
confidence: 99%